1976
DOI: 10.1021/bi00656a016
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the binding of staphylococcal 125I-labeled α-toxin to rabbit erythrocytes

Abstract: Staphylococcal alpha-toxin, a hemolytic exotoxin, can be iodinated using the lactoperoxidase method. 125 I-Labeled alpha-toxin binds to rabbit erythrocytes in an apparently irreversible and highly specific manner. The binding of 125 I-labeled alpha-toxin to erythrocytes of rabbit and human reflects the species specificity of native alpha-toxin. Binding of 125I-labeled alpha-toxin is blocked by the presence of native alpha-toxin, 127I-labeled alpha-toxin, or anti-alpha-toxin antibody. Simultaneous assays of 125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
3
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 20 publications
7
72
3
2
Order By: Relevance
“…However, a high-affinity interaction of the toxin with a proteinaceous eukaryotic receptor has been suggested because rabbit erythrocytes are significantly more sensitive to Hla than human erythrocytes, correlating with the identification of 1,200-5,000 toxin-binding sites per rabbit cell (8, 9). Binding is saturable and time dependent, consistent with a ligand-receptor interaction (8,10). In addition to these data, membrane lipids seem to be central to the interaction of the toxin with the eukaryotic cell.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…However, a high-affinity interaction of the toxin with a proteinaceous eukaryotic receptor has been suggested because rabbit erythrocytes are significantly more sensitive to Hla than human erythrocytes, correlating with the identification of 1,200-5,000 toxin-binding sites per rabbit cell (8, 9). Binding is saturable and time dependent, consistent with a ligand-receptor interaction (8,10). In addition to these data, membrane lipids seem to be central to the interaction of the toxin with the eukaryotic cell.…”
mentioning
confidence: 75%
“…Although the requirement for membrane lipids in toxin biology has been well described, a model proposing these as the sole cell-binding moiety fails to explain several important observations. Most notably, the species specificity of the toxin implies a proteinaceous receptor, because liposomes mirroring rabbit and human red blood cells do not parallel the sensitivities of these cells (10). Further, protease treatment of highly sensitive rabbit red blood cells abrogates toxin binding (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been proposed that one or more of these cell types, not RBC, may be the primary target for AT lysis in human S. aureus infections (7,15,38). Therefore, we tested the purified MAbs for the ability to prevent nAT-mediated lysis of the human cell lines A549 (alveolar epithelial cell line) and THP-1 (monocytic cell line).…”
Section: Monoclonal Antibody Generationmentioning
confidence: 99%
“…Despite considerable effort, the nature of the interaction of the toxin with membranes of sensitive cells is still unclear. From the results of binding studies with toxin which had lost its lytic activity by radioiodination or heating, it was concluded that the high sensitivity of rabbit erythrocytes to toxin-induced lysis was the result of the presence of high specificity toxin receptors on the membrane Harshman, 1973 and1976a;Kato et al, 1975a andBarei and Fackrell, 1979;Lo and Fackrell, 1979), but more recent data support a less specific lytic mechanism involving hydrophobic interaction of toxin with membranes resulting in transmembrane pore formation (Fussle et al, 1981). Our observations on the characteristics of binding of radioiodinated toxin with full haemolytic activity to erythrocytes are reported here.…”
Section: Introductionmentioning
confidence: 99%